THE EFFECT OF SELF-CONCEPT, MOTIVATION AND DISCIPLINE ON THE PERFORMANCE OF THE PRIMARY SCHOOL PRINCIPALS AT JAKARSA REGENCY OF SOUTH JAKARTA - Heru Sriyono (IJHCM (International Journal of Human Capital Management), 2017)
This research was about the effects of self-concept, motivation and discipline on the performance of the primary school principals at Jagakarsa regency of South Jakarta. The objectives of this research were: determining whether self-concept has a direct effect on discipline, determining whether motivation has a direct affect on discipline, determining whether discipline has a direct effect on performance, determining whether the self-concept has direct effect on performance, determining whether the motivation has a direct effect on performance, determining whether the self-concept has an indirect effect on performance but through discipline, and determining whether the motivation have an indirect effect on performance through discipline. The research was conducted by survey method with path-analysis. The sample size was 63 principals of the school. The result are as follows : (1) that the self-concept directly affect the discipline of the principals; (2) the motivation directly affect their discipline, and (3) the discipline directly affect their performance, therefore, improvement of performance of to the principal should be improved by enhancing the rules and working standard.Keyword : self-concept, motivation, discipline, school-principal’sperformance